Development of Chemical Literacy Items in Electrolyte and Non Electrolyte Solution Topic for Class X SMA/MA - Dehvi Qoinun Nisa; Eka Yusmaita (Entalpi Pendidikan Kimia, 2022)
This study aims develop chemical literacy item on electrolyte and non electrolyte solution that can be used measure student’s literacy skill and help student understand the concept of chemistry and apply in solving problems in daily life. The type of research is development with Model of Educational Reconstruction (MER) design. The content validity test was carried out by five validators and analysed using the Rasch model with the Minifacet application. The results of the content validity analysis in this study show the result of the agreement (exact agreements) of 84,6% and the estimated result of approval of 85,3%. The result of the chemical analysis items have a valid category and have reliability of 0,88.